2019
DOI: 10.1111/jsr.12918
|View full text |Cite
|
Sign up to set email alerts
|

Development of sleep–wake rhythms during the first year of age

Abstract: Circadian rhythms refer to biological rhythms that have an endogenous period length of approximately 24 hr. However, not much is known about the variance in the development of the sleep-wake rhythm. The study objectives were (a) to describe the normative variation in the development of a sleep-wake rhythm in infancy, (b) to assess whether slower development is related to sleep quality and (c) to evaluate factors that are related to the slower development of a sleep-wake rhythm. The study is based on a represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
(38 reference statements)
0
10
0
2
Order By: Relevance
“…Previously, it has been reported that regular light exposure during the day is related to better/longer night-time sleep (Harrison 2004;Iwata et al 2016). Moreover, daytime naps are related to later bedtimes, shorter night-time sleeps and poorer sleep quality, both in younger (Paavonen et al 2019) and older children (Akacem et al 2015). Finally, maternal eveningness (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that regular light exposure during the day is related to better/longer night-time sleep (Harrison 2004;Iwata et al 2016). Moreover, daytime naps are related to later bedtimes, shorter night-time sleeps and poorer sleep quality, both in younger (Paavonen et al 2019) and older children (Akacem et al 2015). Finally, maternal eveningness (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…age) (Paavonen et al, 2020;Weissbluth, 1995), and most of the infants sleep an average of two hours during daytime. Interestingly, one recent longitudinal study reported that inappropriate amounts of daytime sleep were related to worse quality of night-time sleep in three to eight-month-old infants (Paavonen et al, 2019). Therefore, it is likely that infants with average amounts of daytime sleep most likely represent the normal ranges of the developmental stage also in other areas of development, such as cognition and/or self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard in short-term infant sleep studies is polysomnography (PSG), a non-invasive technique that combines a large set of physiological signals, recorded overnight, to generate an assessment of sleep behavior ( Grigg-Damberger et al, 2007 ). For long-term studies, infant sleep behavior is assessed with sleep diaries and questionnaires ( Sadeh, 2004 ; Paavonen et al, 2019 ). Recent work has also used wrist- or ankle-worn actigraphy ( Sadeh, 2011 ; Paavonen et al, 2019 ) to provide rough assessments of sleep-wake cycles.…”
Section: Introductionmentioning
confidence: 99%
“…For long-term studies, infant sleep behavior is assessed with sleep diaries and questionnaires ( Sadeh, 2004 ; Paavonen et al, 2019 ). Recent work has also used wrist- or ankle-worn actigraphy ( Sadeh, 2011 ; Paavonen et al, 2019 ) to provide rough assessments of sleep-wake cycles. All of these methods have significant limitations.…”
Section: Introductionmentioning
confidence: 99%